2023
DOI: 10.1111/jhn.13250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pureed and liquidised diets on health‐related quality of life scores in older patients during postacute rehabilitation: A pilot study

Akio Shimizu,
Kohei Yamaguchi,
Haruka Tohara

Abstract: BackgroundConsuming texture‐modified diets was considered to negatively affect health‐related quality of life (HR‐QoL). However, the precise relationship between the levels of food texture consumed and HR‐QoL remains uncertain. The present study aimed to determine the association between levels of food texture consumed and HR‐QoL.MethodsThis cross‐sectional study included 122 hospitalised patients aged ≥ 65 years (mean ± SD age 78.9 ± 7.9 years; 48.4% female) who required postacute rehabilitation. Consumed foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Multiple factors, including age, oral status, and disease burden (1), contribute to these conditions and, in particular, attention should be paid to the diet provided to individuals with dysphagia, including texture-modified foods and thickened liquids. A previous study have shown that the consumption of texture-modified diets is cross-sectionally associated with malnutrition, sarcopenia, and decreased quality of life in individuals with dysphagia (1,2). Because texture-modified diets require special cooking, it is believed that the nutrient density per unit weight is reduced such settings, compared to regular diets (1).…”
Section: Editorial On the Research Topic Malnutrition In Dysphagia: N...mentioning
confidence: 99%
“…Multiple factors, including age, oral status, and disease burden (1), contribute to these conditions and, in particular, attention should be paid to the diet provided to individuals with dysphagia, including texture-modified foods and thickened liquids. A previous study have shown that the consumption of texture-modified diets is cross-sectionally associated with malnutrition, sarcopenia, and decreased quality of life in individuals with dysphagia (1,2). Because texture-modified diets require special cooking, it is believed that the nutrient density per unit weight is reduced such settings, compared to regular diets (1).…”
Section: Editorial On the Research Topic Malnutrition In Dysphagia: N...mentioning
confidence: 99%